Mechanical and neural responses to impact of drop jump for sprint runners and swimmers - Arai, A.; Ishikawa, M.; Urata, T.; Kunimasa, Y.; Sano, K.; Tanaka, H.; Ito, A. (Japanese Journal of Physical Fitness and Sports Medicine, 2015)
The purpose of the present study was to examine the importance of the agonist muscle activity of the post-impact 30 ms phase during drop jump (DJ) for effective rebound performance by comparing those of sprint runners and swimmers. The eight sprint runners (SPRINT) and twelve swimmers (SWIM) were participated in this study. They performed DJ from a 0.3-m height box with maximal rebound efforts. Electromyograms (EMG) of the lower leg muscles (medial gastrocnemius [MG], soleus [SOL] and tibialis anterior [TA]), and vertical ground reaction force together with kinematic data were measured simultaneously during DJ. In addition, the onsets of fascicle stretching of the MG and SOL muscles were measured by using high-speed ultrasonography (521Hz) during DJ. The onsets of the fascicle stretching of SOL during DJ were not significantly different between SPRINT and SWIM (15 ± 7 ms and 16 ± 6 ms, respectively). During DJ, SPRINT showed onset of the SOL EMG before the ground contact (-26 ± 19 ms). Meanwhile, SWIM showed the onset of the SOL EMG after the ground contact of DJ (16 ± 19 ms). These results suggest that the SOL muscles for SWIM cannot be fully-activated during the braking phase. Consequently, the rate of force development during the braking phase of DJ and subsequently rebound height could be reduced in SWIM.